The Emergence of Fritillaria imperialis in Written References of Traditional Persian Medicine: a Historical Review - Afsaneh Bonyadi; Seyyedali Mozaffarpur*; Mohammad Azadbakht; Mortaza Mojahedi (Lorestan University of Medical Sciences, 2017)
Fritillaria plant belongs to the lily family (Liliaceae) and naturally grows in cold areas, highlands, rocky slopes and cliffs. This study examines the emergence of this plant in the written references of Traditional Persian Medicine (TPM). In this research, we searched native names of Fritillaria imperialis (laleh sarnegoun) in outstanding references of TPM including: Almansori fi Teb, Al-Qanon fi Teb, Al-saidana fi Teb, Al-Abnieh an Haghayegh Al-Advieh, Al-Aghraz Al-Tibbia, Ekhtiyarat Badi'i, Al-Mo'tamed fi Al-AdviehAl-Mofrade, Tazkereh-ye Davoud, Tohfeh Al-Momenin, Makhzan Al-Aladvieh and MohitA'azam. Fritillaria is one among thousands of medical materials added to the pharmacopeia books in TPM from Avicenna's era (the 4th century AH) up to the13th century AH. In our review, the first report of Fritillaria was found in the book of Tohfeh Al-Mo'menin written by Hakim Mo'men Tonekaboni. He discovered the therapeutic effect of the oil of Fritillaria imperialis against sciatica. TPM was represented as a dynamic medicine, culture characterized by continual expansion of its written references.